The Metastatic Suppressor Nm23-H1 Interacts with EBNA3C at Sequences Located between the Glutamine- and Proline-Rich Domains and Can Cooperate in Activation of Transcription - Subramanian, Chitra (American Society for Microbiology, 2002)
Epstein-Barr virus (EBV) is a lymphotrophic herpesvirus infecting most of the world's population. It is associated with a number of human lymphoid and epithelial tumors and lymphoproliferative diseases in immunocompromised patients. Recent studies have shown an in vitro and in vivo interaction between the EBV nuclear antigen 3C (EBNA3C) and the metastatic suppressor Nm23-H1, known to be downregulated in human invasive breast carcinoma. In this study, we have identified the domain of EBNA3C that specifically binds to Nm23-H1. This domain lies within the region comprising amino acids 637 to 675 of EBNA3C flanked by the proline- and glutamine-rich domains. Furthermore, we show that Nm23-H1 activates transcription when fused to the Gal4 DNA-binding domain and is coexpressed with a luciferase reporter construct containing the Gal4 binding sites upstream of a basal promoter. Gal4-Nm23-H1, when tethered to the promoter by binding to the Gal4 DNA binding sequences, consistently activated transcription. The level of activation increased when increasing amounts of Gal4-Nm23-H1 were introduced into the system. Moreover, EBNA3C when cotransfected with Gal4-Nm23-H1 enhanced the transcriptional activity. These results suggest that Nm23-H1 may have intrinsic transcription activities in EBV-infected cells and that this activity can be modulated in the presence of the essential latent antigen EBNA3C.